2016
DOI: 10.1016/j.nima.2015.11.157
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a large-area GEM detector read out with wide radial zigzag strips

Abstract: A 1-meter-long trapezoidal Triple-GEM detector with wide readout strips was tested in hadron beams at the Fermilab Test Beam Facility in October 2013. The readout strips have a special zigzag geometry and run along the radial direction with an azimuthal pitch of 1.37 mrad to measure the azimuthal φ-coordinate of incident particles. The zigzag geometry of the readout reduces the required number of electronic channels by a factor of three compared to conventional straight readout strips while preserving good ang… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 17 publications
(13 reference statements)
0
20
0
Order By: Relevance
“…This was confirmed in more recent studies which showed that the spatial resolution of a small GEM detector with parallel zigzag strip or zigzag pad readout can approach 70 µm [4,5]. We subsequently introduced radial zigzag strips to read out trapezoidal large-area GEM detectors [6], which are intended for tracking systems at future experiments, e.g. forward tracking at the electron ion collider (EIC) [7].…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…This was confirmed in more recent studies which showed that the spatial resolution of a small GEM detector with parallel zigzag strip or zigzag pad readout can approach 70 µm [4,5]. We subsequently introduced radial zigzag strips to read out trapezoidal large-area GEM detectors [6], which are intended for tracking systems at future experiments, e.g. forward tracking at the electron ion collider (EIC) [7].…”
Section: Introductionmentioning
confidence: 83%
“…In our previous study [6], a similar zigzag readout structure was tested using hadron beams and the resolution was found to be around 180 µrad at a slightly lower voltage of V drift = 3200 V. We estimate from the measurement of resolution as a function of HV in that previous study that a 140 V increase in V drift corresponds to a 27% improvement in resolution, i.e. at V drift = 3340 V the resolution would be expected to be about 130 µrad.…”
Section: Spatial Resolutionsmentioning
confidence: 89%
See 3 more Smart Citations